PENGEMBANGAN PERBANKAN SYARIAH DENGAN PENDEKATAN TRIPLE CO-SYSTEM - Hasan, Asyari (JURIS (Jurnal Ilmiah Syariah), 2014)
As a barometer of the power of Islam Economy, “Syariah” Bank ideally did a development that was really different compared with the system done by conventional bank in principal side, product, system and organisation. If the main objective of the “Syariah” Bank was to help economy of the society, it had to be involved in doing some activities in order to rich the economy of those society. It did not just improve their income through investing money but also improve the ownership. Therefore, one’s income would increase if the ownership was improved or increased.